Novel Natural Polymer‐Based Hydrogel Patches with Janus Asymmetric‐Adhesion for Emergency Hemostasis and Wound Healing - Sun, Lanfang; Zhou, Junyi; Lai, Jieying; Zheng, Xue; Wang, Hanzhang; Lu, Bin; Huang, Runsheng; Zhang, Li‐Ming (Advanced functional materials, 2024)
An asymmetrical wound dressing functions akin to human skin by serving as a protective barrier between a wound and its immediate environment. However, significant challenges persist concerning the robust adhesion and asymmetrical adhesion properties of hydrogels, particularly when applied in emergency hemostasis and wound healing contexts. Herein, the study has successfully synthesized hydrogel patches with Janus asymmetric‐adhesion, denoted as HGO‐C, exclusively comprised of natural polymers. This achievement is realized through the assembly of adhesive hydrogel (HGO) and non‐adhesive hydrogel (CGC), thereby amalgamating their distinct functionalities. The non‐adhesive hydrogel component served as a physical shield and safeguarding the wound against contamination, while the adhesive hydrogel, when in contacted with the wound surface, firmly adhered to it, swiftly arresting bleeding and facilitating wound healing. Cytocompatibility tests, hemolysis tests, antibacterial assays, and coagulation assays demonstrated excellent biocompatibility, antibacterial, and hemostatic properties of HGO‐C. Finally, the in vivo experiments, including a liver hemorrhage assay and a wound healing assay, unequivocally showed the rapid hemostatic and enhanced wound healing capabilities of HGO‐C. Consequently, these distinctive hydrogel patches, derived from natural polymers and characterized by their asymmetric adhesion properties, may have great potential for real‐life usage in clinical patients. HGO‐C hydrogel patches are successfully synthesized with Janus asymmetric adhesion by merging the adhesive and non‐adhesive hydrogel technologies. Tests have proven HGO‐C hydrogel patches exceptional biocompatibility and hemostatic abilities, with in vivo studies showcasing their remarkable speed in stopping bleeding and promoting wound healing. These natural polymer‐based hydrogel patches hold immense potential for clinical use.